Implementasi Metode Qiro’ati dalam Pembelajaran Al-Qur’an di SMPIT Harapan Umat Kabupaten Brebes - Nailul Munna, Itsna; Priyanto, Dwi (Jurnal Pendidikan Agama Islam, 2025)
This study aims to describe the implementation of the Qiro’ati method in Al-Qur’an learning at SMPIT Harapan Umat, Brebes Regency. A qualitative approach was used in this research. Data collection methods included observation, interviews, and documentation. Data analysis techniques involved data reduction, data presentation, data validation, and drawing conclusions. The research subjects included teachers and students at SMPIT Harapan Umat. The results indicate that the implementation of the Qiro’ati method in Al-Qur’an learning at SMPIT Harapan Umat is carried out effectively. This is evidenced by the students’ ability to recite the Qur’an with tartil, following the rules of tajweed, as well as improvements in makharijul huruf (articulation points of letters) and punctuation. The learning stages included outdoor classical sessions, openings, indoor classical sessions, individual practice, classical review, and closing sessions.